Small Cell Carcinoma of the Ovary of Hypercalcemic Type: A Case Report - Zaied, S. (Hindawi Publishing Corporation, 2012)
Introduction. The small cell carcinoma of hypercalcemic type of ovary is a very aggressive tumor. It is associated with two-thirds of cases with hypercalcemia most often asymptomatic. It occurs mostly for young women. The treatment combines surgery, chemotherapy, and radiotherapy. Case Presentation. We report a case of small cell carcinoma of the ovary hypercalcemic type in a young Tunisian woman aged 25 years after a severe abdominal pain syndrome and a large ovarian mass discovered in scanner; a laparotomy was performed by radical surgery. The pathological examination of the specimen confirmed the diagnosis. The radiological assessment performed after surgery showed a continuing evolution. Palliative chemotherapy was established, and the patient had died two months after diagnosis. Conclusion. The hypercalcemic small cell carcinoma of the ovary is a rare disease of poor prognosis.